The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ans.15990
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for the Nasal Obstruction Symptom Evaluation Scale in the general Australian population

Abstract: Background: Recent changes to the Australian Medicare Benefits Scheme have introduced the NOSE Score as a criteria threshold for funding rhinoplasty. On review of the literature, however, there is minimal normative Nasal Obstruction Symptom Evaluation (NOSE) score data to provide context for these changes. Methods: Participants were recruited according to the general Australian population distribution of age (18-65 years), gender and geographical locations using the market research company Pureprofile. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…The results showed that the postoperative NOSE scores of the patients were significantly lower than those before surgery ( t = 6.31, P < 0.001), indicating that the subjective nasal congestion symptoms of the patients improved. The postoperative NOSE score was closer to the standard NOSE scale score of 16.43 ± 18.89 points of the 18 to 65-year-old population calculated by Stefani et al 23 This result indicated the advantage of an endoscopic-assisted approach in correcting ventilation dysfunction through nasal septoplasty and turbinoplasty. The study preliminarily confirmed that this surgical approach has certain application value in clinical practice.…”
Section: Discussionsupporting
confidence: 71%
“…The results showed that the postoperative NOSE scores of the patients were significantly lower than those before surgery ( t = 6.31, P < 0.001), indicating that the subjective nasal congestion symptoms of the patients improved. The postoperative NOSE score was closer to the standard NOSE scale score of 16.43 ± 18.89 points of the 18 to 65-year-old population calculated by Stefani et al 23 This result indicated the advantage of an endoscopic-assisted approach in correcting ventilation dysfunction through nasal septoplasty and turbinoplasty. The study preliminarily confirmed that this surgical approach has certain application value in clinical practice.…”
Section: Discussionsupporting
confidence: 71%